Pengaruh Infeksi Virus Kerupuk terhadap Pertumbuhan dan Hasil Tanaman Tembakau Payakumbuh: The Effect of Cracker Virus Infection on Growth and Yield of Payakumbuh Tobacco Plant - Mismawarni Srima Ningsih; Fardedi, Syafrison; Giska Oktabriana; Mela Rahmah; Hary Yanto Jailani (Jurusan Budidaya Perkebunan, 2024)
Limapuluh Kota Regency and Payakumbuh City, West Sumatra Province are the centers for the cultivation of Payakumbuh tobacco plants. The average Payakumbuh tobacco production is still low, namely 0.701 tonnes/ha. One of the causes of low productivity is disease caused by the cracker virus. This research aims to see the effect of naturally infected cracker virus infection on the growth and production of tobacco plants. This research is an observational study, carried out from June to September 2023, at the Payakumbuh State Agricultural Polytechnic experimental garden. The data obtained were processed using the T test at the 5%, level using the Statistical Program for Social Science (SPSS) Version 23 software. From observation and data processing it was found that cracker virus infection caused low levels of chlorophyll A, high levels of chlorophyll B and total leaf chlorophyll levels. plant, leaf length, petiole length, leaf length, leaf width, leaf fresh weight, and root fresh weight, but had no effect on the number of leaves and leaf thickness compared to uninfected plants. From this it can be concluded that cracker virus infection can reduce the growth and yield of Payakumbuh tobacco.